Pembangunan Kakas Bantu Pembangkitan Kasus Uji Black-Box Berdasarkan Skenario Penggunaan Sistem - Laode Muhamad Fauzan; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Generally, testing consist of 3 phase,specifically generate test case, execute test case, and evaluate the testing result. Software testing is a process that expend a lot in both time and resources. One way to reduce the time and resources is by automate the test case generation. Test case can be derived from use case scenario. This kind of test case is called black-box test case. Use case scenario has many different formats, this paper will use the Cockburn format. In order to transform the use case scenario. This research use natural language processing and EFSM (Extended Finite State Machine) model. Natural language processing will be used for generating activity table. The activity table will modeled with EFSM and tranversed to produce a test case. This research will develop the tool using java that allows the tools to run on platform that supports JRE (Java Runtime Environment). The tools is tested using unit testing, integration testing, and validation testing. Unit and integration will be conducted with whitebox method, while validation testing is done using black-box method. The tool can generate test case from 20 use case scenario in less than 120 seconds.